The Alliance of NGOs on Crime Prevention & Criminal Justice (Alliance of NGOs on Crime Prevention and Criminal Justice)
"The Alliance brings together a broad network of civil society organizations contributing to the achievement of security and justice for all. It ensures that civil society are recognized and heard in advancing the crime prevention and criminal justice agenda and in designing, implementing and measuring results of relevant policies everywhere. Under the umbrella of the Alliance, cooperation among its members will be strengthened, reinforcing the expertise and vision of each of the members to add value and support the work of relevant international organizations, especially UNODC"